2016
DOI: 10.1007/s11262-016-1383-1
|View full text |Cite
|
Sign up to set email alerts
|

Low genetic diversity of Banana bunchy top virus, with a sub-regional pattern of variation, in Democratic Republic of Congo

Abstract: Banana bunchy top virus (BBTV), belonging to the genus Babuvirus, is the most devastating and widespread banana virus. Banana and plantain are major crops in terms of household income and food security in Democratic Republic of Congo (DRC). Despite the large area under banana and plantain cultivation in the country, before this study, the genetic characterization of BBTV isolates had only been undertaken for two provinces. In the study presented here, genetic variation in BBTV was assessed from 52 BBTV isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Recombination is a major contributor to genetic diversity [ 18 , 74 ] and genetic variations [ 75 ] in ssDNA viruses. Recombination analysis of BBTV components based on nucleotide sequence showed that DNA-U3 exhibits complex intra- and inter recombination patterns ( Fig 3 ) with a recombination occurrence ( Table 7 ) of about 16.8% which is about 9 times more than the least recombined DNA-S component (1.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Recombination is a major contributor to genetic diversity [ 18 , 74 ] and genetic variations [ 75 ] in ssDNA viruses. Recombination analysis of BBTV components based on nucleotide sequence showed that DNA-U3 exhibits complex intra- and inter recombination patterns ( Fig 3 ) with a recombination occurrence ( Table 7 ) of about 16.8% which is about 9 times more than the least recombined DNA-S component (1.8%).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this study was performed to investigate the genetic structure and diversity of the BBTV isolates in the Philippines. Here, the partial DNA-R region of BBTV was sequenced due to its wide application in assessing genetic diversity and other molecular analyses (Bell et al, 2002; Furuya et al, 2005; Amin et al, 2007; Kumar et al, 2011; Shekhawat et al, 2012; Banerjee et al, 2014; Chiaki et al, 2015; Mukwa et al, 2016). Survey and sample collection were conducted in banana growing areas in various regions in the Philippines for BBTV detection and diversity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In-depth studies on the diversity of BBTV from various countries were already reported, such as in Democratic Republic of Congo (Mukwa et al, 2016), Pakistan (Amin et al, 2007), sub-Saharan Africa (Kumar et al, 2011), Indonesia (Chiaki et al, 2015), Japan (Furuya et al, 2005) and India (Banerjee et al, 2014). The information on the degree of genetic diversity and distribution of BBTV in these countries provided useful and fundamental information to control BBTD through various pest management approaches.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important cases is the banana streak viruses (BSVs), because the cultivated banana species are only reproduced by vegetative propagation and BSVs remain inserted into genome indefinitely. Along with BSVs, Banana bunchy top virus (BBTV, family Nanoviridae ) are the most economically important viruses for banana production worldwide (Rybicki, 2015; Mukwa et al, 2016). Interestingly, BBTV is a DNA virus that could be directly targeted using the same transgene-free GES approach.…”
Section: Ges-mediated Plant Virus Defenses Vis-à-vis Gmo Regulationsmentioning
confidence: 99%